Analysis of the Influence of Green Roofs in the reduction of the stormwater runoff hydrograph of a high Andean city in Ayacucho, Peru (LACCEI, 2024)
Use of green technologies in urban drainage systems has shown advantages with respect to traditional systems, such as a reduction in peak flows. This article compares the hydrologic response of a green roof to that of a conventional roof. The objective is to analyze the influence of green roofs in runoff reduction in urban drainage systems. Three different rain intensities, corresponding to return periods of 2, 5 and 10, were tested on a surface of 17.71 m2. Half of the cover was a green roof, and the other half was a tin roof, a conventional roofing system. In addition, slopes were adjusted to 10 %, 25 % and 20 %. Results show a reduction of up to 53 % in peak flows and a reduction of up to 68 % in outflow volumes. The lag time (time to peak discharge) increased in 10.3 minutes.